2013
DOI: 10.1007/s10955-013-0743-7
|View full text |Cite
|
Sign up to set email alerts
|

Short Paths for First Passage Percolation on the Complete Graph

Abstract: We study the random geometry of first passage percolation on the complete graph equipped with independent and identically distributed edge weights, continuing the program initiated by Bhamidi and van der Hofstad [6]. We describe our results in terms of a sequence of parameters (s n ) n≥1 that quantifies the extreme-value behavior of small weights, and that describes different universality classes for first passage percolation on the complete graph. We consider both n-independent as well as n-dependent edge wei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
(263 reference statements)
0
17
0
Order By: Relevance
“…important mathematical model in probability theory that has been studied extensively in grid-like graphs, see e.g. [43,53,73], and on non-spatial (random) graph models as well such as the complete graph [48,37,38,39,56], the Erdős-Rényi graph [14], the configuration model [13,12,50] and the inhomogeneous random graph model [61]. FPP in the 'true' scale-free regime on the configuration model, (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…important mathematical model in probability theory that has been studied extensively in grid-like graphs, see e.g. [43,53,73], and on non-spatial (random) graph models as well such as the complete graph [48,37,38,39,56], the Erdős-Rényi graph [14], the configuration model [13,12,50] and the inhomogeneous random graph model [61]. FPP in the 'true' scale-free regime on the configuration model, (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we study first passage percolation on the complete graph equipped with independent and identically distributed positive and continuous edge weights. In contrast to earlier work [11,12,16,20,27], we consider the case where the extreme values of the edge weights are highly separated.…”
Section: Model and Summary Of Resultsmentioning
confidence: 99%
“…Since H n is integer-valued, it follows that (2.10) must fail in this case. First order asymptotics are investigated in [20], and it is shown that H n /(s n log n)…”
Section: The Universality Class In Terms Of S Nmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to a number of natural questions. The most extensively studied is the "typical distance," quantified by the total weight and number of edges on the shortest path between a pair of random nodes [49][50][51]. It is also possible to analyze the "flooding time" [37,52], defined as the time to reach the last node from a given source node chosen at random.…”
Section: First-passage Percolationmentioning
confidence: 99%